Implementasi Kepemimpinan Kepala Madrasah dalam Pelaksanaan Manajemen Berbasis Madrasah - Fitri Susanti; Ismy Wulansari; Emmi Kholilah Harahap; Hamengkubowono Hamengkubowono (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2023)
The Madrasah as an educational institution that regulates learning activities and in the process of implementing education involves all stakeholders within the scope of problems in madrasah education, namely the quality of educators and administrative staff, inadequate facilities and infrastructure, an unfocused madrasah curriculum and tends to be overloaded, the low quality of education includes: teachers who are less professional in carrying out tasks such as being undisciplined, lack of communication and coordination between school principals and teachers regarding school conditions Kepahiang”. The purpose of this research is to find out the authorities and responsibilities of schools in implementing MBM at MTsN 01 Kepahiang. This research is carried out by using the "purposive sampling" method, which is a sampling technique from data sources with certain considerations. This type of research is descriptive qualitative research with the type of field research.